Regimes of value in museum practices: A networked biography of the MacGregor field collection from British New Guinea. Issue 2 (2nd July 2020) - Torrence, Robin; Bonshek, Elizabeth; Clarke, Anne; M. Davies, Susan; Philp, Jude; Quinnell, Michael
ABSTRACT: Between 1888 and 1898 Sir William MacGregor, first Administrator of British New Guinea, orchestrated the collection of over 15, 000 cultural objects. Using Appadurai's notion of 'things-in-motion', we trace the networked biography of the MacGregor collection through 'regimes of value' as it moved from the territory to museums in Australia and Britain and then repatriated to Papua New Guinea. We show how collection management practices in these institutions were shaped by attitudes about anthropology as an emerging discipline, British New Guinea, and Sir William himself. The social history of the MacGregor collections highlights the multifaceted roles that ethnographic collections have played in sustaining cultural values, strengthening personal ties, re-enforcing self-identity and supporting nation building.